Frozen - De la Cruz, Melissa 1971-; Johnston, Michael (Heart of Dread / De la Cruz, Melissa, 2013)
More than a century after a catastrophic disaster wiped out most of humanity and covered much of the earth with ice, fifteen-year-old Cass yields to the voice in her head urging her to embark on a dangerous journey across a poisoned sea to the mythical land, Blue